Positive electrode active material for lithium ion secondary battery, manufacturing method thereof, and lithium ion secondary battery

The positive electrode active material with a specific compositional formula stabilizes the crystal structure of lithium ion secondary batteries with high nickel content, improving discharge capacity and cycle stability by optimizing additive elements and surface concentration.

JP7618991B2Active Publication Date: 2025-01-22PROTERIAL LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020159279
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-24
Publication Date
2025-01-22
Estimated Expiration
2040-09-24

AI Technical Summary

Technical Problem

Lithium ion secondary batteries with high nickel content face challenges in maintaining crystal structure stability, leading to poor charge-discharge cycle characteristics due to lattice distortion and crystal structure changes during charging and discharging.

Method used

A positive electrode active material with a compositional formula Li1+a Ni b Co c Mn d M1 e Al f O 2+α, where M1 is Ti, and specific atomic concentrations and ratios are optimized to suppress lattice distortion and crystal structure changes, promoting a layered structure and surface concentration of M1, thereby enhancing discharge capacity and cycle stability.

Benefits of technology

The solution achieves high discharge capacity and good charge-discharge cycle characteristics in lithium ion secondary batteries, even with a high nickel content, by stabilizing the crystal structure and reducing lattice distortion through optimized additive elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618991000003
    Figure 0007618991000003
  • Figure 0007618991000004
    Figure 0007618991000004
  • Figure 0007618991000005
    Figure 0007618991000005
Patent Text Reader

Abstract

To provide a positive electrode active material for a lithium ion secondary battery, which has a Ni ratio of 80% or more and is good in discharge capacity, rate characteristics and cycle characteristics.SOLUTION: A positive electrode active material for a lithium ion secondary battery includes a lithium transition metal composite oxide represented by the following composition formula (1): Li1+aNibCocMndM1eAlfO2+α (1) [M1 represents one or more elements selected from among Ti, Ga, Mg, Zr and Zn, and a, b, c, d, e, f and α satisfy -0.04≤a≤0.08, 0.80≤b<1.0, 0≤c<0.2, 0≤d<0.2, 0<e<0.08, 0<f<0.04, 0<e+f<0.08, b+c+d+e+f=1 and -0.2<α<0.2.]. An atomic concentration D1 of M1 and an atomic concentration D2 of Al at the interface between primary particles at the inside of a secondary particle, and an atomic concentration D3 of M1 and an atomic concentration D4 of Al in the central part of each primary particle satisfy D1>D3 and D1 / D3>D2 / D4.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a method for producing the same, and a lithium ion secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries are widely used as lightweight secondary batteries with high energy density. As the range of applications of lithium-ion secondary batteries expands, there is a demand for higher capacity and excellent charge / discharge cycle characteristics.

[0003] Under these circumstances, in addition to establishing high capacity and mass production, studies are being conducted on the positive electrode active material, which greatly affects the battery characteristics, in terms of reducing the lithium ion insertion / extraction resistance and diffusion resistance, stabilizing the crystal structure, etc. As a positive electrode active material for lithium ion secondary batteries, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure (hereinafter sometimes referred to as a layered structure) are widely known. As an oxide having a layered structure, LiCoO2 has traditionally been used, but due to demands for high capacity and mass production, ternary systems represented by Li(Ni,Co,Mn)O2 and nickel systems in which LiNiO2 is substituted with different elements have been developed.

[0004] Among lithium transition metal composite oxides with a layered structure, nickel-based oxides have the disadvantage of not necessarily having good life characteristics. However, nickel-based oxides are composed of nickel, which is cheaper than cobalt and other metals, and have relatively high capacity, so they are expected to be used in a variety of applications. In particular, there are high expectations for chemical compositions with a high ratio of nickel per metal other than lithium (Ni, Co, Mn, etc.).

[0005] For example, Patent Document 1 describes a fired fine and uniform mixture of a main component raw material of a lithium transition metal compound and a compound (additive) composed of a metal element that can have a valence of 5 or 6. The additive element has a continuous compositional gradient structure with a concentration gradient in the depth direction from the particle surface, specifically in the range of about 10 nm in depth, and is characterized as a lithium transition metal compound powder for a positive electrode material of a lithium secondary battery.

[0006] Also, Patent Document 2 describes Li 1+a Ni b Mn c Co d Ti e M f O 2+α …(1) (However, in the above formula (1), M is at least one element selected from the group consisting of Mg, Al, Zr, Mo, and Nb, and a, b, c, d, e, f, and α are numbers satisfying -0.1 ≦ a ≦ 0.2, 0.7 < b ≦ 0.9, 0 ≦ c < 0.3, 0 ≦ d < 0.3, 0 < e ≦ 0.25, 0 ≦ f < 0.3, b + c + d + e + f = 1, and -0.2 ≦ α ≦ 0.2.) It is represented by, and based on X-ray photoelectron spectroscopy, the atomic ratio of Ti 3+ and Ti 4+ Ti 3+ / Ti 4+ is 1.5 or more and 20 or less, and a positive electrode material for a lithium ion secondary battery is described.

[0007] Furthermore, Patent Document 3 describes a first coating layer composed of any one or more lithium metal oxides of lithium titanate, lithium tantalate, lithium zirconate, and lithium tungstate on lithium nickel cobalt manganate, and a second coating layer composed of aluminum oxide on the first coating layer, and a positive electrode material for a lithium ion secondary battery is described.

Prior Art Documents

Patent Documents

[0008]

Patent Document 1

[0009] Nickel-based oxides with a high nickel content, in which the ratio of nickel per metal excluding lithium is 70% or more, have the disadvantage that it is difficult to achieve good charge-discharge cycle characteristics due to the low stability of the crystal structure. In general, lithium transition metal composite oxides with a high nickel content have a tendency to have unstable crystal structures during charging and discharging. In the crystal structure, Ni forms layers composed of MeO2 (Me represents a metal element such as Ni). During discharging, lithium ions are inserted between these layers to occupy the lithium sites, and during discharging, the lithium ions are released. Such insertion and release of lithium ions causes lattice distortion or crystal structure changes that affect charge-discharge cycle characteristics. Therefore, in order to suppress lattice distortion and crystal structure changes, there is a method of adding stable additive elements that do not contribute to charging and discharging.

[0010] The above-mentioned Patent Documents 1 and 2 suppress lattice distortion and crystal structure change by forming a concentration gradient or a surface concentrated layer due to the added element on the surface of the Ni-Co-Mn-based positive electrode active material, and obtain a certain effect. In addition, Patent Document 3 obtains a certain effect in improving cycle characteristics by further forming a coating layer. However, if the ratio of nickel is increased to 80% or more for the purpose of increasing capacity, etc., it becomes even more difficult to maintain stability. In addition, the presence of a coating layer increases resistance, and there are concerns about a decrease in discharge capacity and output. Furthermore, since stability is maintained with a relatively large amount of cobalt, productivity including raw material costs is poor. Therefore, a high discharge capacity and good charge / discharge cycle characteristics are required in a positive electrode active material with a higher Ni ratio and a lower Co ratio, or which does not contain Co.

[0011] Therefore, the present invention relates to a positive electrode active material with a high Ni ratio in which the ratio of Ni is 80% or more, and a positive electrode active material for a lithium-ion secondary battery having a high discharge capacity and good charge-discharge cycle characteristics (hereinafter, may be simply referred to as "positive electrode active material"). Furthermore, the present invention aims to provide a positive electrode active material having the same characteristics even when the Co content is further reduced or Co is not contained, a method for manufacturing the same, and a lithium-ion secondary battery using this positive electrode active material.

Means for Solving the Problems

[0012] The positive electrode active material for a lithium-ion secondary battery according to the present invention is the following compositional formula (1); Li 1+a Ni b Co c Mn d M1 e Al f O 2+α ···(1) [However, in the compositional formula (1), M1 is Ti where a, b, c, d, e, f, and α are numbers satisfying -0.04 ≦ a ≦ 0.08, 0.80 ≦ b < 1.0, 0 ≦ c ≦0.06 , 0 ≦ d < 0.2, 0 < e < 0.08, 0 < f < 0.04, 0 < e + f < 0.08, b + c + d + e + f = 1, and -0.2 < α < 0.2.], a positive electrode active material for a lithium-ion secondary battery containing a lithium transition metal composite oxide represented by the formula, wherein the positive electrode active material includes secondary particles formed by aggregation of a plurality of primary particles, and in the primary particles inside the secondary particles, the atomic concentration D1 of M1 and the atomic concentration D2 of Al at the interface between the primary particles, and the atomic concentration D3 of M1 and the atomic concentration D4 of Al at the center of the primary particles satisfy D1 > D3 and D1 / D3 > D2 / D4.

[0013] The method for manufacturing a positive electrode active material for a lithium-ion secondary battery according to the present invention is the following compositional formula (1); Li 1+a Nib Co c Mn d M1 e Al f O 2+α ···(1) [However, in the compositional formula (1), M1 is Ti where a, b, c, d, e, f, and α are numbers satisfying -0.04 ≦ a ≦ 0.08, 0.80 ≦ b < 1.0, 0 ≦ c ≦0.06 , 0 ≦ d < 0.2, 0 < e < 0.08, 0 < f < 0.04, 0 < e + f < 0.08, b + c + d + e + f = 1, and -0.2 < α < 0.2. A method for producing a positive electrode active material for a lithium-ion secondary battery containing a lithium transition metal composite oxide represented by a granulation or coprecipitation step of obtaining granulated bodies, and a firing step of firing the granulated bodies in an oxidizing atmosphere to obtain a lithium composite compound having a chemical composition represented by the compositional formula (1), and in the primary particles inside the secondary particles, the atomic concentration D1 of M1 and the atomic concentration D2 of Al at the interface between the primary particles, and the atomic concentration D3 of M1 and the atomic concentration D4 of Al at the center of the primary particles satisfy D1 > D3 and D1 / D3 > D2 / D4. A method for producing a positive electrode active material for a lithium-ion secondary battery having

[0014] According to the present invention, in a positive electrode active material with a high Ni ratio of 80% or more of the Ni ratio, a positive electrode active material for a lithium-ion secondary battery having a high discharge capacity and good charge-discharge cycle characteristics can be provided. In particular, even in a positive electrode active material having a Ni ratio of 80% or more and a Co ratio of 6% or less, a high discharge capacity and good charge-discharge cycle characteristics can be exhibited.

Brief Description of the Drawings

[0015] [Figure 1] A partial cross-sectional view schematically showing an example of a lithium-ion secondary battery. [Diagram 2] A diagram schematically showing an example of secondary particles and primary particles of the positive electrode active material of the present invention. [Diagram 3]FIG. 2 is a diagram showing a STEM image of a primary particle in Example 1 of the present invention and measurement points of each element by EDX analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a positive electrode active material for a lithium ion secondary battery according to one embodiment of the present invention, a method for producing the same, and a lithium ion secondary battery using the same will be described in detail.

[0017] <Cathode active material> The positive electrode active material according to the present embodiment includes a lithium transition metal composite oxide having a layered α-NaFeO2 type crystal structure and containing lithium and a transition metal. This positive electrode active material is mainly composed of primary particles of the lithium transition metal composite oxide and secondary particles formed by agglomeration of a plurality of primary particles. The lithium transition metal composite oxide has a layered structure as a main phase that allows insertion and desorption of lithium ions.

[0018] The positive electrode active material according to this embodiment may contain, in addition to the lithium transition metal composite oxide which is the main component, unavoidable impurities derived from the raw materials or the manufacturing process, other components which coat the lithium transition metal composite oxide particles, such as a boron component, a phosphorus component, a sulfur component, a fluorine component, an organic substance, and other components which are mixed together with the lithium transition metal composite oxide particles.

[0019] The lithium transition metal composite oxide according to this embodiment is represented by the following composition formula (1). Li 1+a Ni b Co c Mn d M1 e Al f O 2+α (1) [However, in Composition Formula (1), M1 is one or more elements selected from the group consisting of Ti, Ga, Mg, Zr, and Zn, and a, b, c, d, e, f, and α are, respectively, -0.04 ≦ a ≦ 0.08, 0.80 ≦ b < 1.0, 0 ≦ c < 0.2, 0 ≦ d < 0.2, 0 < e < 0.08, 0 < f < 0.04, 0 < e + f < 0.08, b + c + d + e + f = 1, and -0.2 < α < 0.2, which are numbers satisfying these conditions.]

[0020] The lithium transition metal composite oxide represented by Composition Formula (1) has a nickel ratio of 80% or more per metal excluding lithium. That is, in terms of the atomic fraction with respect to the total of Ni, Co, Mn, M1, and Al, Ni is contained at 80 at% or more. Since the nickel content is high, it is a nickel-based oxide capable of achieving a high discharge capacity. Also, because the nickel content is high, the raw material cost is lower compared to LiCoO2, etc., and it is excellent from the perspective of productivity including raw material costs.

[0021] Generally, a lithium transition metal composite oxide with a high nickel content has the property that its crystal structure tends to become unstable during charge and discharge. In the crystal structure, Ni forms a layer composed of MeO2 (Me represents a metal element such as Ni). During discharge, lithium ions are inserted between these layers to occupy lithium sites, and during charge, the lithium ions desorb. Since a large amount of nickel exists at the transition metal sites of the layer composed of MeO2, when the valence of nickel changes for charge compensation accompanying the insertion and desorption of lithium ions, a large lattice strain or crystal structure change occurs. Such lattice strain or crystal structure change occurring with the insertion and desorption of lithium ions affects the discharge capacity characteristics and charge-discharge cycle characteristics.

[0022] Therefore, as described above, there is a method of adding a stable additive element that does not contribute to charging and discharging in order to suppress lattice distortion and crystal structure changes. The above-mentioned Patent Documents 1 and 2 are examples of such a method, but in the past, only the surface of the secondary particles, in other words, the primary particles on the surface that constitute the secondary particles, were modified, and there was room for improvement in the internal primary particles that constitute the secondary particles. Therefore, in this embodiment, attention is paid to individual primary particles located inside the secondary particles, and the influence of the additive element is examined.

[0023] As a result, in each primary particle (hereinafter, sometimes simply referred to as a primary particle) located inside the secondary particle, by increasing the atomic concentration of M1 in the composition formula on the surface, the lattice distortion and crystal structure change in the vicinity of the surface of the primary particle due to the change in the valence of Ni are reduced, and the lattice distortion and crystal structure change of the secondary particle can be further suppressed. As a result, good charge-discharge cycle characteristics can be obtained. In addition, by simultaneously adding M1 and Al in the composition formula, Al promotes the formation of a layered structure and the temperature at which the layered structure is formed is lowered, so that the difference between the temperature at which the layered structure is formed and the reaction temperature of Li and M1, which occurs at a temperature higher than the layered structure formation, becomes large, and the surface concentration of M1 is promoted. As a result, it has been found that the atomic concentration of M1 on the surface is increased, and the charge-discharge cycle characteristics are further improved while maintaining the discharge capacity. The definitions of the atomic concentration of M1 and the interface, surface and center of the primary particle will be described later.

[0024] (chemical composition) Here, the significance of the chemical composition represented by the composition formula (1) will be explained.

[0025] In the composition formula (1), a is -0.04 or more and 0.08 or less. a represents the excess or deficiency of lithium with respect to the stoichiometric ratio Li(Ni,Co,Mn,M1,Al)O2. a is not the charge value at the time of raw material synthesis, but the value in the lithium transition metal composite oxide obtained by firing. If the excess or deficiency of lithium in the composition formula (1) is excessive, that is, if the composition has too little lithium or too much lithium relative to the total of Ni, Co, Mn, M1 and Al, the synthesis reaction does not proceed properly during firing, and cation mixing in which nickel is mixed into the lithium site is likely to occur, or crystallinity is likely to decrease. In particular, when the proportion of nickel is increased to 80% or more, the occurrence of such cation mixing and the decrease in crystallinity are likely to become significant, and the discharge capacity and charge / discharge cycle characteristics are likely to be impaired. On the other hand, if a is within the above-mentioned numerical range, cation mixing is reduced, and various battery performances can be improved. Therefore, even in a composition with a high nickel content, a high discharge capacity and good charge / discharge cycle characteristics can be obtained.

[0026] a is preferably -0.03 or more and 0.06 or less. When a is -0.03 or more and 0.06 or less, the excess or deficiency of lithium with respect to the stoichiometric ratio is smaller, so that the synthesis reaction proceeds appropriately during firing, and cation mixing is less likely to occur. Therefore, a layered structure with fewer defects is formed, and high discharge capacity and good charge / discharge cycle characteristics can be obtained. In addition, for the positive electrode active material mainly composed of a lithium transition metal composite oxide represented by composition formula (1), the ratio of the atomic concentration (number of moles) of lithium contained in the positive electrode active material to the total atomic concentration (number of moles) of metal elements other than lithium is preferably 0.96 or more and 1.08 or less, and more preferably 0.97 or more and 1.06 or less. The fired precursor fired by heat treatment may be contaminated with other components, and there is a risk that the reaction ratio during firing may deviate from the stoichiometric ratio. However, with such an atomic concentration ratio, there is a high possibility that cation mixing and a decrease in crystallinity are suppressed based on the chemical composition represented by composition formula (1) during firing. Therefore, a positive electrode active material that improves the performance of various batteries can be obtained.

[0027] The above describes the preferred range of a in the state of a powder produced as a positive electrode active material. However, when the positive electrode active material represented by composition formula (1) is incorporated in the positive electrode of a lithium ion secondary battery, charge and discharge accompanied by insertion and desorption of Li are performed, so that a is preferably in the range of −0.9 to 0.06.

[0028] The nickel coefficient b in the composition formula (1) is 0.80 or more and less than 1.00. When b is 0.80 or more, a higher discharge capacity can be obtained compared to other nickel-based oxides with a low nickel content or ternary oxides represented by Li(Ni,Co,M1)O2. In addition, the amount of transition metals that are rarer than nickel can be reduced, which reduces raw material costs.

[0029] The nickel coefficient b may be 0.85 or more, 0.90 or more, or 0.92 or more. The larger b is, the higher the discharge capacity tends to be. The nickel coefficient b may be 0.95 or less, 0.90 or less, or 0.85 or less. The smaller b is, the smaller the lattice distortion or crystal structure change associated with the insertion or desorption of lithium ions becomes, and the less likely cation mixing in which nickel is mixed into the lithium site or the less likely the crystallinity is reduced during firing, so that good rate characteristics and charge / discharge cycle characteristics tend to be obtained.

[0030] The coefficient c of cobalt in the composition formula (1) is 0 or more and less than 0.2. Cobalt may be added intentionally, or may have a composition ratio equivalent to unavoidable impurities. When the cobalt is in the above range, the crystal structure becomes more stable, and effects such as suppression of cation mixing in which nickel is mixed into the lithium site can be obtained. Therefore, high discharge capacity and good charge-discharge cycle characteristics can be obtained. On the other hand, if the cobalt is excessive, the raw material cost of the positive electrode active material increases. In addition, the ratio of other transition metals such as nickel decreases, and there is a risk that the discharge capacity will be low or the effect of the metal element represented by M1 will be reduced. On the other hand, if c is in the above numerical range, the raw material cost of the lithium transition metal composite oxide that shows high discharge capacity, good rate characteristics and charge-discharge cycle characteristics can be reduced.

[0031] The cobalt coefficient c may be 0.01 or more, 0.02 or more, 0.03 or more, or 0.04 or more. The larger c is, the more effective the effect of the element substitution of cobalt is, so that better charge / discharge cycle characteristics and the like tend to be obtained. The cobalt coefficient c may be 0.06 or less, 0.03 or less, or 0.01 or less. The smaller c is, the more the raw material cost can be reduced. In this embodiment, when the nickel coefficient b is 0.90 or more, the cobalt coefficient c can be 0 or more and 0.03 or less. The more cobalt is added, the more stable the crystal structure becomes, and the effect of suppressing cation mixing in which nickel is mixed into the lithium site can be obtained, while when the nickel coefficient b is 0.90 or more, there is originally little room for adding cobalt, and it is considered that the amount of cobalt can be reduced by the effect of stabilizing the crystal structure near the primary particle surface due to the concentration of M1 on the primary particle surface.

[0032] Although manganese in the composition formula (1) is a transition metal, it is believed to remain stable at +4 even during charging and discharging. Therefore, the use of manganese has the effect of stabilizing the crystal structure during charging and discharging.

[0033] The manganese coefficient d in the composition formula (1) is 0 or more and less than 0.2. If manganese is excessive, the ratio of other transition metals such as nickel will be low, and the discharge capacity of the positive electrode active material may be low. On the other hand, if d is within the above-mentioned numerical range, a higher discharge capacity and charge / discharge cycle characteristics tend to be obtained.

[0034] The manganese coefficient d may be 0.01 or more, 0.03 or more, 0.05 or more, or 0.10 or more. The larger d is, the more effectively the effect of the elemental substitution of manganese is obtained. The manganese coefficient d may be 0.15 or less, 0.10 or less, or 0.05 or less. The smaller d is, the higher the proportion of other transition metals such as nickel, and the higher the discharge capacity tends to be.

[0035] M1 in the composition formula (1) is at least one element selected from the group consisting of Ti, Ga, Mg, Zr, and Zn. (Hereinafter referred to as M1). These elements react with Li to form a concentrated layer after Li and Ni react to form an α-NaFeO2 type crystal structure exhibiting a layered structure. In this case, M1 is present on the primary particle surface of the positive electrode active material in the relatively low-temperature sintering process where the reaction between Li and Ni begins, and M1 is likely to form a concentrated layer on the primary particle surface in the subsequent high-temperature sintering process. In particular, by using a solid-phase method to premix all elements including M1 except Li and pulverize them, or by premixing all elements including Li and M1 and pulverizing them, M1 can be distributed on the primary particle surface. In addition, it is more preferable to contain at least Ti. Ti can be tetravalent, so it has a strong bond with O and has a large effect of stabilizing the crystal structure. In addition, this is because the molecular weight is relatively small, and the theoretical capacity of the positive electrode active material is reduced only slightly when it is added. By using metal elements with such properties, it is possible to concentrate and distribute them on the surface of the primary particles by selecting appropriate synthesis conditions. Therefore, by using these metal elements M1, the effect of suppressing the deterioration of the crystal structure from the surface of the positive electrode active material during charging and discharging can be obtained.

[0036] The coefficient e of M1 in the composition formula (1) is set to be more than 0 and less than 0.08. When M1 is added, the crystal structure of the surface of the positive electrode active material becomes more stable as described above, and good charge-discharge cycle characteristics can be obtained. On the other hand, if M1 is excessive, the ratio of other transition metals such as nickel decreases, the discharge capacity decreases, or the effect of stabilizing the crystal structure by manganese decreases, and the charge-discharge cycle characteristics may decrease. In addition, when M1 is Ti or the like that can be tetravalent, the ratio of divalent nickel increases relatively near the surface of the primary particles, and cation mixing is likely to occur. On the other hand, if e is within the above-mentioned numerical range, a lithium transition metal composite oxide exhibiting high discharge capacity and good charge-discharge cycle characteristics can be obtained. The coefficient e of M1 is preferably 0.01 or more and 0.05 or less, more preferably 0.01 or more and 0.03 or less. When e is 0.01 or more, the ratio of nickel on the surface of the primary particles decreases, and the change in the crystal structure on the surface of the primary particles is reduced. On the other hand, when e is 0.05 or less, the ratio of other transition metals such as nickel can be sufficiently maintained, and a high discharge capacity can be obtained. Therefore, a layered structure with fewer defects is formed, and a high discharge capacity and good charge-discharge cycle characteristics can be obtained.

[0037] The aluminum in the composition formula (1) does not form a concentrated layer on the surface of the primary particles, but is uniformly dissolved inside the primary particles. The use of aluminum actually promotes the surface concentration of M1, lowering the proportion of nickel on the primary particle surface. This reduces changes in the crystal structure near the surface of the primary particles.

[0038] The coefficient f of aluminum in the composition formula (1) is set to be more than 0 and less than 0.04. When aluminum is added, the crystal structure near the surface of the positive electrode active material becomes more stable as described above, and good charge-discharge cycle characteristics can be obtained. On the other hand, if aluminum is excessive, the ratio of other transition metals such as nickel decreases, the discharge capacity decreases, or the effect of stabilizing the crystal structure by manganese decreases, and the charge-discharge cycle characteristics may decrease. The coefficient f of aluminum is preferably 0.01 or more and less than 0.04, and more preferably 0.01 or more and 0.02 or less. When f is 0.01 or more, the ratio of M1 on the surface of the primary particles increases, and as a result, the ratio of nickel on the surface of the primary particles decreases, and the change in the crystal structure near the surface of the primary particles is reduced. On the other hand, when f is less than 0.04, the ratio of other transition metals such as nickel can be sufficiently maintained, and a high discharge capacity can be obtained. Therefore, a layered structure with fewer defects is formed, and a high discharge capacity and charge-discharge cycle characteristics can be obtained.

[0039] The sum e+f of the coefficient e of M1 and the coefficient f of aluminum in the composition formula (1) is greater than 0 and less than 0.08. If M1 and aluminum are in excess, the ratio of other transition metals such as nickel will be reduced, resulting in a lower discharge capacity and a lower effect of stabilizing the crystal structure by manganese, which may result in a deterioration in charge-discharge cycle characteristics. The ratio e / f of the coefficient e of M1 and the coefficient f of aluminum is preferably 0.5 or more and 5 or less. If e / f is 0.5 or more, the coefficient e of M1 is relatively high, which makes it possible to increase the ratio of M1 on the surface of the primary particles, which is preferable. If e / f is 5 or less, the coefficient f of aluminum is relatively high, which makes it possible to obtain an effect of promoting the surface concentration of M1 by adding aluminum, which is preferable. Moreover, e / f is more preferably 1.0 or more and 3 or less. If e / f is 1.0 or more and 3 or less, the atomic concentration D1 of M1 at the interface between the primary particles will be high, which will result in a lower ratio of nickel on the surface of the primary particles, resulting in good charge-discharge cycle characteristics.

[0040] In the composition formula (1), α is greater than -0.2 and less than 0.2. α represents the excess or deficiency of oxygen relative to the stoichiometric ratio of Li(Ni,Co,Mn,M1,Al)O2. If α is within the above-mentioned numerical range, the crystal structure has few defects, and the appropriate crystal structure can provide high discharge capacity and good charge / discharge cycle characteristics. The value of α can be measured by inert gas fusion-infrared absorption method.

[0041] (Secondary particles) The average particle size of the primary particles of the positive electrode active material is preferably 0.05 μm or more and 2 μm or less. By making the average particle size of the primary particles of the positive electrode active material 2 μm or less, a reaction field of the positive electrode active material can be secured, and a high discharge capacity can be obtained. It is more preferably 1.5 μm or less, and even more preferably 1.0 μm or less. In addition, the average particle size of the secondary particles of the positive electrode active material is preferably, for example, 3 μm or more and 50 μm or less.

[0042] The secondary particles (granules) of the positive electrode active material can be obtained by granulating the primary particles produced by the method for producing the positive electrode active material described below, by dry granulation or wet granulation. As the granulation means, for example, a granulator such as a spray dryer or a tumbling fluidized bed device can be used.

[0043] The lithium transition metal composite oxide represented by the composition formula (1) preferably has a BET specific surface area of ​​0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more. The BET specific surface area is preferably 1.5 m 2 / g or less, more preferably 1.2m 2 / g or less. BET specific surface area is 0.1m 2 When the BET specific surface area is 1.5 m / g or more, a positive electrode having a sufficiently high molding density and a sufficiently high packing rate of the positive electrode active material can be obtained. 2When the lithium transition metal composite oxide has a molecular weight of 0.1 to 1.0 g / g or less, the lithium transition metal composite oxide is less likely to break, deform, or fall off when it is pressed into shape or when the volume of the oxide changes during charging and discharging, and the pores are prevented from sucking up the binder. This improves the coatability and adhesion of the positive electrode active material, resulting in a high discharge capacity and good charge and discharge cycle characteristics.

[0044] (Primary particles that make up secondary particles) The positive electrode active material according to the embodiment of the present invention includes secondary particles formed by agglomeration of a plurality of primary particles of a lithium transition metal composite oxide, and the inside of the secondary particle is configured such that a plurality of primary particles are adjacent to each other via an interface (surface). However, not all primary particles form an interface, but many primary particles may form an interface. In the primary particles inside the secondary particle, the atomic concentration D1 (at%) of M1 and the atomic concentration D2 (at%) of Al at the interface (which may be called the surface of the primary particle), and the atomic concentration D3 (at%) of M1 and the atomic concentration D4 (at%) of Al at the center of the primary particle are preferably D1>D3 and satisfy the relationship D1 / D3>D2 / D4. In other words, it can be said that M1 is concentrated on the surface, while aluminum is uniformly dissolved inside the particle. Here, the atomic concentrations D1 and D3 of M1 are expressed as (M1 / (Ni+Co+Mn+M1+Al)), and the atomic concentrations D2 and D4 of aluminum are expressed as (Al / (Ni+Co+Mn+M1+Al), and can be confirmed by EDX or the like. It is essential that the primary particles in which M1 is concentrated on the surface and in which aluminum is uniformly dissolved are primary particles excluding the primary particles located on the surfaces of the secondary particles, and it is desirable that at least 50% or more, preferably 70% or more, and more preferably 100% of the number of internal primary particles are primary particles in which M1 is concentrated on the surface and in which aluminum is uniformly dissolved.

[0045] It is effective that the surface-enriched layer exists not only on the surface of the secondary particles but also on each primary particle inside the secondary particles. Even if the M1-enriched layer is very thin, the proportion of Ni is relatively decreased, so that the crystal structure near the surface becomes more stable, leading to good charge-discharge cycle characteristics. In addition, if the M1-enriched layer exists only on the surface of the secondary particles, the deterioration of the crystal structure starts from the surface of the primary particles when the electrolyte that has penetrated into the secondary particles comes into contact with the secondary particles, which causes the charge-discharge cycle characteristics to deteriorate. The concentration D1 of M1 on the surface of the primary particles is used as an indicator of the presence of a layer of M1-enriched on the surface of the primary particles. The center of the primary particles is defined as the range from the surface of the primary particles to a depth of 0.2r or more toward the center of the primary particles, where r is the average particle diameter of the primary particles.

[0046] The atomic concentrations D1 and D3 of M1 are preferably D1>(100×e)≧D3. When D1>(100×e), the concentration of M1 near the surface of the primary particles is higher than that when M1 is uniformly distributed in the primary particles, so the Ni ratio on the surface of the primary particles is relatively lower. Therefore, the crystal structure near the surface becomes more stable, and good charge-discharge cycle characteristics can be obtained. In addition, it is more preferable that D1>(3.5×(100×e). The Ni ratio on the surface is further lower. On the other hand, when (100×e)≧D3, the concentration of M1 in the center of the primary particles is equal to or lower than that when M1 is uniformly distributed in the primary particles, so it is considered that M1 forms a concentrated layer other than the center, for example, near the surface. In addition, when D3>(100×e / 4), M1 is present not only near the surface of the primary particles but also diffused to the center, so there is no large difference between the surface and center in the expansion and contraction of the crystal structure accompanying the insertion and desorption of Li during the charge-discharge cycle, and good charge-discharge cycle characteristics can be obtained.

[0047] In addition, the atomic concentrations D1 and D3 of M1 are preferably such that D1 is 3.5 times or more than D3. If D1 is 3.5 times or more than D3, M1 is sufficiently concentrated near the surface of the primary particles, and the Ni ratio near the surface of the primary particles is relatively reduced. Therefore, the crystal structure near the surface becomes more stable, and good charge-discharge cycle characteristics can be obtained. More preferably, D1 is 3.7 times or more than D3. Also, it is more preferable that D1 is 30 times or less than D3. If the difference between D1 and D3 is too large, Ni, Co, Mn, and Al will relatively have a large concentration difference between the surface and the center of the primary particles. Therefore, there is a large difference between the expansion and contraction of the crystal structure due to the insertion and desorption of Li during the charge-discharge cycle, and the concentrated layer of M1 may be isolated due to the difference in expansion and contraction.

[0048] In addition, it is preferable that the difference in concentration of Co, Mn, and Al between the surface and the center of the primary particle is smaller than the difference in concentration of M1. If the difference in concentration of Co, Mn, and Al between the surface and the center of the primary particle is smaller than the difference in concentration of M1, there is no large difference in the expansion and contraction of the crystal structure caused by the insertion and desorption of Li between the surface and the center. Therefore, good charge and discharge cycle characteristics are obtained.

[0049] The average composition of the particles of the positive electrode active material can be confirmed by inductively coupled plasma (ICP), atomic absorption spectrometry (AAS), etc. The atomic concentrations of M1 and aluminum in the primary particles of the positive electrode active material can be quantitatively analyzed for the concentrations of Ni, Co, Mn, M1, and Al using a scanning transmission electron microscope (STEM) and energy dispersive X-ray spectrometry (EDX) on a cross-section of the positive electrode active material.

[0050] <Method of manufacturing positive electrode active material> The positive electrode active material according to the present embodiment can be produced by ensuring the synthesis reaction between lithium and nickel, cobalt, etc. under appropriate firing conditions under a raw material ratio such that the lithium transition metal composite oxide has a chemical composition represented by composition formula (1). The method for producing the positive electrode active material according to the present embodiment will be described below.

[0051] The method for producing a positive electrode active material for a lithium ion secondary battery according to this embodiment includes a step of obtaining granules by either a granulation step or a coprecipitation step, and a firing step of firing the granules under an oxidizing atmosphere. Other steps may be added. For example, a mixing step of mixing the granules with lithium carbonate or lithium hydroxide may be added. In addition, if a large amount of lithium hydroxide or lithium carbonate remains in the positive electrode active material obtained in the firing step, the electrode mixture in the form of a slurry gels in the mixture coating step for producing a positive electrode, so that the remaining lithium hydroxide or lithium carbonate can be reduced by adding a water washing step and a drying step following the firing step. In addition, when the water washing and drying steps are added, the positive electrode active material obtained after the water washing and drying steps satisfies composition formula (1). In the case where the process ends with the firing step, the positive electrode active material obtained after the firing step satisfies composition formula (1). This is because the value of a in the positive electrode active material in the state in which it is used in a battery is important.

[0052] When the granules are obtained by a granulation process, a raw material mixing process is performed before the granulation process. A compound containing lithium may be mixed with a compound containing a metal element other than Li in the composition formula (1), or only a compound containing a metal element other than Li in the composition formula (1) may be mixed. From the viewpoint of dispersing Li more uniformly, it is preferable to mix a compound containing lithium with a compound containing a metal element other than Li in the composition formula (1). For example, by weighing each of these raw materials, grinding and mixing, a powdery mixture in which the raw materials are uniformly mixed can be obtained. As a grinder for grinding the raw materials, for example, a general precision grinder such as a ball mill, a bead mill, a jet mill, a rod mill, a sand mill, etc. can be used. The grinding of the raw materials may be dry grinding or wet grinding. After the dry grinding, a solvent such as water may be added to form a slurry composed of the raw materials and the solvent, or a solvent such as water may be added to the raw materials in advance to form a slurry and then wet grinding. From the viewpoint of obtaining a uniform and fine powder with an average particle size of 0.3 μm or less, it is more preferable to perform wet grinding using a medium such as water. It is also preferable to disperse the raw materials uniformly. For example, in wet mixing, a dispersant can be used to improve the dispersibility of the raw materials in the slurry. Improved dispersibility of the raw materials is preferable because it eliminates unevenness in the thickness of the thickened layer of M1. The dispersant can be a polycarboxylic acid-based, urethane-based, or acrylic resin-based one, with acrylic resin-based being preferred. The amount of dispersant added can be adjusted to adjust the viscosity of the slurry.

[0053] In the granulation step, the mixture obtained in the raw material mixing step is granulated to obtain secondary particles (granules) in which particles are aggregated together. The mixture may be granulated by either dry granulation or wet granulation. For granulation of the mixture, a suitable granulation method such as a rolling granulation method, a fluidized bed granulation method, a compression granulation method, or a spray granulation method may be used. As a granulation method for granulating the mixture, spray granulation is particularly preferred. As a spray granulator, various types such as a two-fluid nozzle type, a four-fluid nozzle type, and a disk type can be used. With the spray granulation method, the slurry precisely mixed and pulverized by wet pulverization can be granulated while drying. In addition, by adjusting the concentration of the slurry, the spray pressure, the disk rotation speed, etc., it is possible to precisely control the particle size of the secondary particles within a predetermined range, and granules that are close to true spheres and have a uniform chemical composition can be efficiently obtained. In the granulation step, it is preferable to granulate the mixture obtained in the mixing step so that the average particle size (D50) is 3 μm or more and 50 μm or less. In this embodiment, the secondary particles of the granules more preferably have an average particle size (D50) of 5 μm or more and 20 μm or less.

[0054] When the granules are obtained by a coprecipitation process, the coprecipitate may be obtained by adjusting the pH of an aqueous solution containing Ni, Co, Mn, M1, and Al. Ni, Co, Mn, M1, and Al may all be coprecipitated at once, or one or more of Ni, Co, Mn, M1, and Al may be coprecipitated (precipitated) and then the other elements may be precipitated (coprecipitated) simultaneously or separately on the surface of the coprecipitate.

[0055] When granules are obtained by mixing only compounds containing metal elements other than Li in the composition formula (1) in the granulation step, and when granules are obtained in the coprecipitation step, the granules are mixed with the lithium compound. The mixing of the granules with the lithium compound can be performed by dry mixing. For example, a V-type mixer or an attritor can be used as a mixer for mixing the granules with the lithium compound. In addition, the granules may be heat-treated before mixing with the lithium compound. The particle strength of the granules is increased, and the lithium compound can be mixed without breaking the granules.

[0056] Examples of the lithium-containing compound include lithium carbonate, lithium acetate, lithium nitrate, lithium hydroxide, lithium chloride, and lithium sulfate. In addition, it is preferable to use lithium carbonate or lithium hydroxide, since the gas generated in the calcination step is water vapor or carbon dioxide gas, which causes less damage to the manufacturing equipment and is excellent in industrial applicability and practicality. In particular, it is more preferable to use at least lithium carbonate, and it is more preferable to use lithium carbonate at a ratio of 80 mass% or more in the lithium-containing raw material. Lithium carbonate is easily available because it is inexpensive and has excellent supply stability compared to other lithium-containing compounds. In addition, lithium carbonate is weakly alkaline, which causes less damage to the manufacturing equipment and is excellent in industrial applicability and practicality.

[0057] Compounds containing metal elements other than Li are preferably composed of C, H, O, and N, such as carbonates, hydroxides, oxyhydroxides, acetates, citrates, and oxides. From the viewpoint of ease of pulverization and the amount of gas released by thermal decomposition, carbonates, hydroxides, and oxides are particularly preferable. Sulfates may also be used. They are easily dissolved in solvents such as water, and are therefore preferable.

[0058] The atomic concentration ratio (molar ratio) of the lithium atomic concentration (number of moles) contained in the calcination precursor to the total atomic concentration (number of moles) of metal elements other than lithium is preferably about 1:1 as per the stoichiometric ratio. A lithium transition metal composite oxide is obtained in which the proportion of divalent nickel occupying the transition metal site is high and the lattice distortion or crystal structure change associated with the insertion and desorption of lithium ions is reduced. In addition, the atomic concentration ratio (molar ratio) of the lithium atomic concentration (number of moles) contained in the calcination precursor to the total atomic concentration (number of moles) of metal elements other than lithium is more preferably 0.98 or more and 1.07 or less. However, during calcination, the lithium contained in the calcination precursor may react with the calcination container or volatilize. Considering that a part of the lithium is lost due to reaction with the calcination container or evaporation during calcination, it is not prohibited to add an excess of lithium at the time of charging.

[0059] In the calcination step, the granules are heat-treated to calcinate the lithium transition metal composite oxide represented by composition formula (1). The calcination step may be a single-stage heat treatment in which the heat treatment temperature is controlled within a fixed range, or may be a multi-stage heat treatment in which the heat treatment temperatures are controlled within different ranges. However, from the viewpoint of obtaining a lithium transition metal composite oxide having high crystal purity, high discharge capacity, and good rate characteristics and charge / discharge cycle characteristics, it is preferable to include a first heat treatment step and a second heat treatment step, and it is essential to satisfy the conditions of the first heat treatment step and the second heat treatment step.

[0060] The first heat treatment step is a heat treatment step in an oxidizing atmosphere at a heat treatment temperature of 400°C or more and less than 750°C for 2 hours or more and 50 hours or less to obtain a first precursor. The main purpose of the first heat treatment step is to remove moisture or carbonate components by a reaction between a lithium compound and a nickel compound, etc., and to generate a crystal of a lithium transition metal composite oxide. The nickel in the calcined precursor is sufficiently oxidized to suppress cation mixing in which nickel is mixed into the lithium site, and to suppress the generation of cubic domains by nickel. In addition, in order to reduce lattice distortion or crystal structure changes associated with the insertion and desorption of lithium ions, manganese is sufficiently oxidized to increase the uniformity of the composition of the layer composed of MeO2 and increase the proportion of divalent nickel with a large ionic radius.

[0061] In the second heat treatment step, the first precursor obtained in the first heat treatment step is heat-treated at a heat treatment temperature of 700° C. to 900° C. for 2 hours to 100 hours to obtain a lithium transition metal composite oxide. The main purpose of the second heat treatment step is to grow the crystal grains of the lithium transition metal composite oxide having a layered structure to an appropriate grain size and specific surface area.

[0062] In the second heat treatment step, if the heat treatment temperature is 700°C or higher, nickel can be sufficiently oxidized to suppress cation mixing, while the crystal grains of the lithium transition metal composite oxide can be grown to an appropriate grain size and specific surface area. In addition, manganese can be sufficiently oxidized to increase the proportion of divalent nickel. Since a main phase is formed in which the lattice constant of the a-axis is large and the lattice distortion or crystal structure change associated with the insertion and desorption of lithium ions is reduced, high discharge capacity, good charge / discharge cycle characteristics, and output characteristics can be obtained. In addition, if the heat treatment temperature is 900°C or lower, lithium is unlikely to volatilize and the layered structure is unlikely to decompose, so that a lithium transition metal composite oxide with high crystal purity and good discharge capacity, charge / discharge cycle characteristics, etc. can be obtained.

[0063] In the firing step, as a heat treatment means, an appropriate heat treatment device can be used, such as a rotary kiln or other rotary furnace, a roller hearth kiln, a tunnel furnace, a pusher furnace or other continuous furnace, a batch furnace, etc. The first heat treatment step and the second heat treatment step may be performed using the same heat treatment device, or different heat treatment devices may be used.

[0064] By going through the above granulation step or coprecipitation step and the calcination step, a positive electrode active material composed of a lithium transition metal composite oxide represented by composition formula (1) can be manufactured. The distribution of M1, the amount of cation mixing, and the specific surface area can be controlled mainly by adjusting the method of preparing the precursor before heat treatment, the composition ratio of metal elements such as nickel, the amount of unreacted lithium hydroxide and lithium carbonate remaining in the first precursor, and the heat treatment temperature and heat treatment time in the second heat treatment step. In the chemical composition represented by composition formula (1), if M1 is concentrated on the surface of the primary particles, aluminum is uniformly solid-dissolved in the primary particles, and cation mixing is sufficiently reduced, an excellent positive electrode active material exhibiting high discharge capacity and good charge / discharge cycle characteristics can be obtained.

[0065] For the purpose of removing impurities, the synthesized lithium transition metal composite oxide may be subjected to a washing step of washing with deionized water or the like, a drying step of drying the washed lithium transition metal composite oxide, etc., after the firing step. The synthesized lithium transition metal composite oxide may also be subjected to a crushing step of crushing the lithium transition metal composite oxide, a classification step of classifying the lithium transition metal composite oxide into a predetermined particle size, etc.

[0066] In the water washing step, the lithium transition metal composite oxide obtained in the baking step is washed with water. The lithium transition metal composite oxide can be washed with water by an appropriate method such as a method of immersing the lithium transition metal composite oxide in water or a method of passing water through the lithium transition metal composite oxide. By washing the lithium transition metal composite oxide with water, it is possible to remove residual alkaline components such as lithium carbonate and lithium hydroxide remaining on the surface or near the surface layer of the lithium transition metal composite oxide. The water in which the lithium transition metal composite oxide is immersed may be still water or may be stirred. As the water, pure water such as deionized water and distilled water, ultrapure water, etc. can be used. In the water washing step, when the lithium transition metal composite oxide is immersed in water, the solid content ratio of the lithium transition metal composite oxide to the water to be immersed is preferably 33% by mass or more and 77% by mass or less. If the solid content ratio is 33% by mass or more, the amount of lithium eluted from the lithium transition metal composite oxide into the water can be reduced. Therefore, a positive electrode active material exhibiting a high discharge capacity and a good rate can be obtained. Also, if the solid content ratio is 77% by mass or less, the powder can be washed uniformly with water, so that impurities can be reliably removed. The time for washing the lithium transition metal composite oxide with water is preferably 20 minutes or less, more preferably 10 minutes or less. If the time for washing with water is 20 minutes or less, the amount of lithium eluted from the lithium transition metal composite oxide into water can be reduced. Therefore, a positive electrode active material exhibiting a high discharge capacity and good charge / discharge cycle characteristics can be obtained.

[0067] The lithium transition metal composite oxide immersed in water can be recovered by an appropriate solid-liquid separation operation. Examples of the solid-liquid separation method include vacuum filtration, pressure filtration, filter press, roller press, and centrifugation. The moisture content of the lithium transition metal composite oxide separated from the water is preferably 20% by mass or less, more preferably 10% by mass or less. If the moisture content is low like this, the lithium compound dissolved in the water will not be reprecipitated in large amounts, so that the performance of the positive electrode active material can be prevented from decreasing. The moisture content of the lithium transition metal composite oxide after solid-liquid separation can be measured, for example, using an infrared moisture meter.

[0068] In the drying step, the lithium transition metal composite oxide washed in the washing step is dried. By drying the lithium transition metal composite oxide, moisture that reacts with the components of the electrolyte to deteriorate the battery or changes the binder to cause coating defects is removed. In addition, by passing through the washing step and the drying step, the surface of the lithium transition metal composite oxide is modified, and the compressibility of the powder of the positive electrode active material is improved. For example, reduced pressure drying, heat drying, reduced pressure heat drying, etc. can be used as the drying method. The atmosphere in the drying step is an inert gas atmosphere not containing carbon dioxide or a highly vacuum reduced pressure atmosphere, which prevents lithium carbonate or lithium hydroxide from being mixed in due to a reaction with carbon dioxide or moisture in the atmosphere. The drying temperature in the drying step is preferably 300°C or less, more preferably 80°C or more and 300°C or less. If the drying temperature is 300°C or less, side reactions can be suppressed while drying, so that deterioration of the performance of the positive electrode active material can be avoided. In addition, if the drying temperature is 80°C or more, moisture can be sufficiently removed in a short time. The moisture content of the lithium transition metal composite oxide after drying is preferably 500ppm or less, more preferably 300ppm or less, and even more preferably 250ppm or less. The moisture content of the lithium transition metal composite oxide after drying can be measured by the Karl Fischer method.

[0069] In the drying step, it is preferable to perform two or more stages of drying treatment with different drying conditions. Specifically, it is preferable for the drying step to have a first drying step and a second drying step. By performing such a multi-stage drying treatment, it is possible to prevent the powder surface of the lithium transition metal composite oxide from being altered due to rapid drying. Therefore, it is possible to prevent a decrease in the drying speed due to the alteration of the powder surface.

[0070] In the first drying step, the lithium transition metal composite oxide washed in the water washing step is dried at a drying temperature of 80° C. or more and 100° C. or less. In the first drying step, most of the moisture present on the particle surfaces of the lithium transition metal composite oxide is removed mainly at the drying rate during the constant rate drying period. In the first drying step, if the drying temperature is 80° C. or higher, a large amount of water can be removed in a short time. If the drying temperature is 100° C. or lower, deterioration of the powder surface of the lithium transition metal composite oxide, which tends to occur at high temperatures, can be suppressed. The drying time in the first drying step is preferably 10 hours or more and 20 hours or less. When the drying time is within this range, most of the moisture present on the particle surfaces of the lithium transition metal composite oxide can be removed even at a relatively low drying temperature at which deterioration of the powder surface of the lithium transition metal composite oxide is suppressed.

[0071] In the second drying step, the lithium transition metal composite oxide dried in the first drying step is dried at a drying temperature of 190° C. or more and 300° C. or less. In the second drying step S42, the moisture present in the vicinity of the particle surface layers of the lithium transition metal composite oxide is reduced while suppressing side reactions that deteriorate the performance of the positive electrode active material, thereby obtaining a lithium transition metal composite oxide dried to an appropriate moisture content. In the second drying step, if the drying temperature is 190° C. or higher, the moisture that has penetrated into the vicinity of the surface layer of the lithium transition metal composite oxide particles can be sufficiently removed, and if the drying temperature is 300° C. or lower, drying can be performed while suppressing side reactions that deteriorate the performance of the positive electrode active material. The drying time in the second drying step is preferably 10 hours or more and 20 hours or less. When the drying time is within this range, side reactions that deteriorate the performance of the positive electrode active material can be suppressed, and the lithium transition metal composite oxide can be dried to a sufficiently low moisture content.

[0072] <Lithium-ion secondary battery> Next, a lithium ion secondary battery using, in the positive electrode, a positive electrode active material (positive electrode active material for lithium ion secondary batteries) containing the above-mentioned lithium transition metal composite oxide will be described. FIG. 1 is a partial cross-sectional view that illustrates a schematic diagram of an example of a lithium ion secondary battery. As shown in FIG. 1, the lithium ion secondary battery 100 includes a cylindrical battery can 101 with a bottom that contains a non-aqueous electrolyte, a wound electrode group 110 contained inside the battery can 101, and a disk-shaped battery lid 102 that seals the opening at the top of the battery can 101. The battery can 101 and the battery lid 102 are made of a metal material such as stainless steel or aluminum. The positive electrode 111 includes a positive electrode current collector 111a and a positive electrode mixture layer 111b formed on the surface of the positive electrode current collector 111a. The negative electrode 112 includes a negative electrode current collector 112a and a negative electrode mixture layer 112b formed on the surface of the negative electrode current collector 112a.

[0073] The positive electrode current collector 111a is formed of, for example, a metal foil such as aluminum or an aluminum alloy, an expanded metal, a punched metal, or the like. The positive electrode mixture layer 111b includes a positive electrode active material containing the lithium transition metal composite oxide. The positive electrode mixture layer 111b is formed of, for example, a positive electrode mixture obtained by mixing a positive electrode active material with a conductive material, a binder, and the like. The negative electrode current collector 112a is formed of a metal foil such as copper, a copper alloy, nickel, or a nickel alloy, an expanded metal, or a punched metal. The negative electrode mixture layer 112b contains a negative electrode active material for a lithium ion secondary battery. The negative electrode mixture layer 112b is formed of a negative electrode mixture obtained by mixing, for example, a negative electrode active material with a conductive material, a binder, and the like. The negative electrode active material, conductive material, binder, and the like may be of appropriate types used in general lithium ion secondary batteries.

[0074] 1, the positive electrode current collector 111a is electrically connected to the battery lid 102 via a positive electrode lead piece 103. Meanwhile, the negative electrode current collector 112a is electrically connected to the bottom of the battery can 101 via a negative electrode lead piece 104. An insulating plate 105 for preventing short circuits is disposed between the wound electrode group 110 and the battery lid 102, and between the wound electrode group 110 and the bottom of the battery can 101. A nonaqueous electrolyte is injected into the battery can 101.

[0075] This lithium ion secondary battery 100 is cylindrical in shape, but the shape and battery structure of the lithium ion secondary battery are not particularly limited, and the battery may have any suitable shape, such as a rectangular shape, a button shape, a laminate sheet shape, or other battery structure. The lithium ion secondary battery according to the present embodiment can be used for various applications. Examples of applications include, but are not limited to, small power sources for portable electronic devices, household electrical appliances, and the like, stationary power sources for power storage devices, uninterruptible power sources, power leveling devices, and the like, and driving power sources for ships, railroad vehicles, hybrid railroad vehicles, hybrid automobiles, electric automobiles, and the like. The lithium transition metal composite oxide has a high nickel content, and exhibits high discharge capacity as well as good charge and discharge cycle characteristics, and is therefore particularly suitable for use in vehicles that require a long life.

[0076] The chemical composition of the positive electrode active material used in a lithium-ion secondary battery can be confirmed by disassembling the battery, extracting the positive electrode active material that constitutes the positive electrode, and performing high-frequency inductively coupled plasma atomic emission spectrometry, atomic absorption spectrometry, etc. Since the composition ratio of lithium (1+a in composition formula (1)) depends on the state of charge, the chemical composition of the positive electrode active material can also be determined based on whether the lithium coefficient a satisfies -0.9≦a≦0.08. EXAMPLES

[0077] The present invention will be specifically described below with reference to examples, but the technical scope of the present invention is not limited to these examples.

[0078] Positive electrode active materials according to the examples of the present invention were synthesized and evaluated for element distribution, discharge capacity, and charge / discharge cycle characteristics (capacity retention rate). As a control for the examples, positive electrode active materials according to comparative examples having different chemical compositions were synthesized and similarly evaluated.

[0079] [Example 1] First, lithium carbonate, nickel hydroxide, cobalt carbonate, manganese carbonate, titanium oxide, and aluminum oxide were prepared as raw materials, and each raw material was weighed out so that the molar ratio of metal elements was Li:Ni:Co:Mn:Ti:Al was 1.03:0.85:0.03:0.09:0.01:0.02, and pure water was added so that the solid content ratio was 30 mass%. Then, the raw material slurry was prepared by wet grinding (wet mixing) in a grinder so that the average particle size was less than 0.2 μm (raw material mixing process).

[0080] Next, the obtained raw material slurry was spray-dried using a nozzle-type spray dryer (Okawahara Chemical Engineering Co., Ltd., ODL-20 type) to obtain D 50 Granules having a particle size of 12 μm were obtained (granulation step). The spray pressure was 0.13 MPa, and the spray amount was 260 g / min. The dried granules were then heat-treated to calcinate the lithium transition metal composite oxide (calcination step). Specifically, the granules were dehydrated in a continuous conveying furnace under air atmosphere at 400° C. for 5 hours. Then, in a calcination furnace replaced with an oxygen gas atmosphere, the granules were heat-treated in an oxygen stream at 700° C. for 6 hours to obtain a first precursor (first heat treatment step). Thereafter, the first precursor was heat-treated in an oxygen stream at 820° C. for 10 hours in a calcination furnace replaced with an oxygen gas atmosphere (second heat treatment step) to obtain a lithium transition metal composite oxide (second heat treatment step). The calcined powder obtained by calcination was classified using a sieve with an opening of 53 μm, and the powder that fell under the sieve was used as the positive electrode active material of the sample.

[0081] [Example 2] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti:Al was 1.03:0.85:0.03:0.09:0.02:0.01.

[0082] [Example 3] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti:Al was 1.03:0.85:0.03:0.08:0.02:0.02.

[0083] [Example 4] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti:Al was 1.03:0.85:0.03:0.08:0.03:0.01.

[0084] [Example 5] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti:Al was 1.03:0.85:0.03:0.05:0.03:0.03.

[0085] [Example 6] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti:Al was 1.03:0.88:0.03:0.05:0.03:0.01.

[0086] [Example 7] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti:Al was 1.03:0.90:0.03:0.03:0.03:0.01.

[0087] [Comparative Example 1] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti was 1.03:0.85:0.03:0.10:0.02.

[0088] [Comparative Example 2] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti was 1.03:0.85:0.03:0.09:0.03.

[0089] [Comparative Example 3] A positive electrode active material was obtained in the same manner as in Example 1, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti was 1.03:0.90:0.03:0.05:0.02.

[0090] [Example 8] First, nickel hydroxide, cobalt carbonate, manganese carbonate, titanium oxide, and aluminum oxide were prepared as raw materials, and each raw material was weighed so that the molar ratio of metal elements was Ni:Co:Mn:Ti:Al of 0.88:0.03:0.05:0.03:0.01, and pure water was added so that the solid content ratio was 20 mass%. Then, the raw material slurry was prepared by wet grinding (wet mixing) in a grinder so that the average particle size was less than 0.2 μm (raw material mixing process).

[0091] Next, the obtained raw material slurry was spray-dried using a nozzle-type spray dryer (Okawahara Chemical Engineering Co., Ltd., ODL-20 type) to obtain D 50 A granule having a particle size of 12 μm was obtained (granulation step). The spray pressure was 0.13 MPa, and the spray amount was 260 g / min. The dried granule was then heat-treated at 650° C. to calcinate the transition metal composite oxide (calcination step). Lithium hydroxide and the obtained transition metal composite oxide were weighed out so that the molar ratio of Li:transition metal was 1.03:1.00, and mixed using a V-type mixer. Then, in a calcination furnace replaced with an oxygen gas atmosphere, the mixture was heat-treated in an oxygen stream at 500° C. for 10 hours to obtain a first precursor (first heat treatment step). Thereafter, the first precursor was heat-treated in an oxygen stream at 820° C. for 32 hours in a calcination furnace replaced with an oxygen gas atmosphere (second heat treatment step) to obtain a lithium transition metal composite oxide (second heat treatment step). The calcined powder obtained by calcination was classified using a sieve with an opening of 53 μm, and the powder that fell under the sieve was used as the positive electrode active material of the sample.

[0092] [Comparative Example 4] A positive electrode active material was obtained in the same manner as in Example 8, except that the raw materials were weighed out so that the molar ratio of Li:Ni:Co:Mn:Ti was 1.03:0.85:0.03:0.09:0.03.

[0093] (Measurement of the chemical composition of the positive electrode active material) The chemical composition of the synthesized positive electrode active material was analyzed by high-frequency inductively coupled plasma atomic emission spectrometry using an ICP-AES optical emission spectrometer "OPTIMA8300" (manufactured by PerkinElmer). The oxygen amount (α in composition formula (1)) of the positive electrode active material was also analyzed by inert gas fusion-infrared absorption method. As a result, the positive electrode active materials according to Examples 1 to 8 and the positive electrode active materials according to Comparative Examples 1 to 4 all had chemical compositions as shown in Table 1, except that only lithium was different from the charged amount.

[0094] (Element concentration distribution) The concentration distribution of M1 and Al in the synthesized positive electrode active material was measured by the following procedure. First, the powder of the prepared positive electrode active material was processed by FIB processing at an acceleration voltage of 30 kV (sampling) and 10 kV (finishing) using a focused ion / electron beam processing and observation device "nano DUET NB5000" (manufactured by Hitachi High-Technologies Corporation) to make it thin. Next, the primary particle interface (surface) inside the secondary particle was identified by STEM observation using a scanning transmission electron microscope "JEM-ARM200F" (manufactured by JEOL Ltd.). Then, the concentration D1 of M1 and the concentration D2 of Al at the primary particle interface inside the secondary particle, and the concentration D3 of M1 and the concentration D4 of Al at the center of the primary particle were measured using an energy dispersive X-ray analyzer "JED-2300T" (manufactured by JEOL Ltd.). The measurement points were two, and the average values ​​were used. The results are shown in Table 1.

[0095] FIG. 2(a) shows an example of a secondary particle of a positive electrode active material for a lithium ion secondary battery, and FIG. 2(b) shows an example of a primary particle. As shown in FIG. 2(a), the positive electrode active material contains secondary particles formed by agglomeration of a plurality of primary particles, and the primary particle surface is also present inside the secondary particle. The surfaces of adjacent primary particles are in contact with each other to form an interface (see FIG. 3). As shown in FIG. 2(b), the atomic concentrations D1 and D2 of M1 and Al at the interface of each primary particle, and the atomic concentrations D3 and D4 of M1 and Al at a depth of 0.2r or more from the surface are measured. Note that the interface and the surface are essentially synonymous, and in this specification, the term "interface of a primary particle" may be rephrased as "surface of a primary particle".

[0096] FIG. 3 shows a STEM image of a primary particle inside a secondary particle in Example 1, and EDX analysis points at the interface (surface) and center. In addition, the concentrations (at%) of Ni, Co, Mn, M1(Ti), and Al at the interface and center of the primary particles of the examples and comparative examples were measured. The results are shown in Table 2.

[0097] (positive electrode) A lithium ion secondary battery was produced using the synthesized positive electrode active material as a positive electrode material, and the discharge capacity and capacity retention rate of the lithium ion secondary battery were determined. First, the produced positive electrode active material, a carbon-based conductive material, and a binder dissolved in advance in N-methyl-2-pyrrolidone (NMP) were mixed in a mass ratio of 94:4.5:1.5. Then, the uniformly mixed positive electrode mixture slurry was applied to a positive electrode current collector made of aluminum foil with a thickness of 20 μm in an amount of 10 mg / cm. 2 The positive electrode mixture slurry applied to the positive electrode current collector was then heat-treated at 120°C to remove the solvent, thereby forming a positive electrode mixture layer. The positive electrode mixture layer was then pressurized by a hot press and punched into a circular shape with a diameter of 15 mm to form a positive electrode.

[0098] (discharge capacity) Next, a lithium ion secondary battery was produced using the produced positive electrode, negative electrode, and separator. Metallic lithium punched into a circle with a diameter of 16 mm was used as the negative electrode. A porous separator made of polypropylene with a thickness of 30 μm was used as the separator. The positive electrode and the negative electrode were opposed to each other in a non-aqueous electrolyte via the separator, and a lithium ion secondary battery was assembled. As the non-aqueous electrolyte, a solution was used in which LiPF6 was dissolved at 1.0 mol / L in a solvent in which ethylene carbonate and dimethyl carbonate were mixed at a volume ratio of 3:7.

[0099] The fabricated lithium ion secondary battery was charged in an environment of 25° C. at a constant current / constant voltage of 40 A / kg based on the mass of the positive electrode mixture and an upper limit potential of 4.3 V. Then, it was discharged at a constant current of 40 A / kg based on the mass of the positive electrode mixture to a lower limit potential of 2.5 V, and the discharge capacity (initial capacity) was measured.

[0100] (Charge / discharge cycle characteristics (capacity retention rate)) A lithium ion secondary battery was produced using the prepared positive electrode, negative electrode, and separator. A negative electrode was used as the negative electrode, which was made by applying graphite to a copper foil negative electrode final current collector, and punched out into a circular shape with a diameter of 16 mm. A 30 μm thick porous separator made of polypropylene was used as the separator. The positive electrode and the negative electrode were opposed to each other in a non-aqueous electrolyte via the separator, and a lithium ion secondary battery was assembled. As the non-aqueous electrolyte, a solution was used in which LiPF6 was dissolved to 1.0 mol / L in a solvent in which ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 3:7, and further 1.5 mass % of vinylene carbonate was dissolved.

[0101] The lithium ion secondary battery thus fabricated was charged at a constant current / constant voltage of 200A / kg based on the mass of the positive electrode mixture and an upper limit potential of 4.2V in an environment of 50°C. Then, a total of 100 cycles of discharging to a lower limit potential of 2.5V at a constant current of 200A / kg based on the mass of the positive electrode mixture were performed, and the discharge capacity after 100 cycles was measured. The ratio of the discharge capacity after 100 cycles to the initial capacity was calculated as the capacity retention rate. The results are shown in Table 1.

[0102] [Table 1]

[0103] [Table 2]

[0104] As shown in Table 1, in Examples 1 to 8, the chemical composition represented by the composition formula (1) was satisfied, D1>D3, and D1 / D3>D2 / D4. Moreover, e / f in Examples 1 to 8 was in the range of 0.5≦e / f≦5. In particular, in Example 1, e / f was 0.5, which is a higher Al content than M1, but D1>D3, and it was found that Ti was concentrated on the surface. From this, it was found that Al was uniformly dissolved in solid solution and Ti was concentrated on the surface, regardless of the ratio of Ti to Al. Moreover, D1 / D3 was 3.3 or less in Comparative Examples 1 to 4 in which Al was not added, whereas it was 3.5 or more in Examples 1 to 8 in which Al was added, and it was found that the surface concentration of Ti was promoted by adding Al. It is known that Al reduces the LiNiO2 formation energy, and it is considered that the addition of Al reduces the LiNiO2 formation temperature, and the difference between the LiNiO2 formation temperature and the temperature at which Ti starts to dissolve in LiNiO2 increases, and the surface concentration of Ti is promoted. This phenomenon may also occur when the content of Al is greater than the content of Ti, so it is believed that even when the content of Al is greater than the content of Ti, Al is uniformly dissolved in solid solution and Ti is concentrated on the surface. As a result, it was confirmed that the examples of the present invention obtained a high discharge capacity exceeding 190 Ah / kg, and the capacity retention rate also showed 79% or more, and were excellent in charge-discharge cycle characteristics. In other words, it was confirmed that when the chemical composition represented by the composition formula (1) is satisfied, D1>D3, and D1 / D3>D2 / D4, it is possible to improve the charge-discharge cycle characteristics while maintaining a high discharge capacity. In particular, in Examples 1 to 2 and 4 to 8 in which D1 / D3 is 3.7 or more, a capacity retention rate of 80% or more was obtained. Furthermore, in Examples 4 to 6 in which the interface Ni ratio is less than 70%, a capacity retention rate of 90% or more was obtained. [Explanation of symbols]

[0105] 100 Lithium-ion secondary battery 101 Battery Can 102 Battery cover 103 Positive electrode lead piece 104 Negative electrode lead piece 105 Insulating plate 106 Sealing material 110 wound electrode group 111 Positive electrode 111a Positive electrode current collector 111b Positive electrode mixture layer 112 Negative electrode 112a Negative electrode current collector 112b Negative electrode mixture layer 113 Separator

Claims

1. The following composition formula (1): Li 1+a Ni b Co c Mn d M1 e Al f O 2+α ・・・(1) [wherein, in composition formula (1), M1 is Ti, and a, b, c, d, e, f, and α are numbers that satisfy, respectively, −0.04≦a≦0.08, 0.80≦b<1.0, 0≦c≦0.06, 0≦d<0.2, 0<e<0.08, 0<f<0.04, 0<e+f<0.08, b+c+d+e+f=1, and −0.2<α<0.2], The positive electrode active material includes secondary particles formed by agglomeration of a plurality of primary particles, A positive electrode active material for a lithium ion secondary battery, characterized in that, in a primary particle inside the secondary particle, an atomic concentration D1 of M1 and an atomic concentration D2 of Al at an interface between the primary particles, and an atomic concentration D3 of M1 and an atomic concentration D4 of Al at a center of the primary particle are D1>D3 and D1 / D3>D2 / D4.

2. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the coefficient e of M1 and the coefficient f of Al are in the range of 0.5≦e / f≦5.

3. The positive electrode active material for a lithium ion secondary battery according to claim 1 or 2, wherein the D1 is 3.7 times or more the D3.

4. A positive electrode active material for a lithium ion secondary battery as described in claim 3, wherein the coefficient d of Mn is 0.01≦d<0.

2.

5. A lithium ion secondary battery comprising a positive electrode containing the positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 4.

6. The following composition formula (1): Li 1+a Ni b Co c Mn d M1 e Al f O 2+α ・・・(1) [In the composition formula (1), M1 is Ti, and a, b, c, d, e, f and α are numbers satisfying −0.04≦a≦0.08, 0.80≦b<1.0, 0≦c≦0.06, 0≦d<0.2, 0<e<0.08, 0<f<0.04, 0<e+f<0.08, b+c+d+e+f=1, and −0.2<α<0.2, respectively. and a firing step of firing the granules in an oxidizing atmosphere to obtain a lithium composite compound having a chemical composition represented by composition formula (1), wherein, in primary particles inside secondary particles, an atomic concentration D1 of M1 and an atomic concentration D2 of Al at an interface between the primary particles, an atomic concentration D3 of M1 and an atomic concentration D4 of Al at a center of the primary particles satisfy D1>D3 and D1 / D3>D2 / D4.

Citation Information

Patent Citations

  • Ternary positive electrode material and preparation method thereof, lithium ion battery and electric vehicle

    CN110867576A

  • Clutching apparatus for rail in rail gas pressure welser

    JP1979028251A

  • Optical pumping laser

    JP1986097981A

  • Positive electrode active material, positive electrode, and lithium ion secondary battery

    JP2016095980A

  • Positive electrode active material for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery

    JP2016225300A